2021
DOI: 10.1101/2021.06.15.21258953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interferon Gamma Release Assays for Latent Mycobacterium tuberculosis Detection in Elderly Hispanics

Abstract: SUMMARY Background. Aging is a tuberculosis comorbidity. Interferon Gamma Release Assays (IGRAs) are used to detect latent Mycobacterium tuberculosis (M.tb) infection (LTBI) in adults, but their performance in the elderly is not well established. We aim to evaluate the performance of IGRAs for LTBI detection in healthy elderly Hispanics with recent, remote or no history of M.tb exposure. Study Design and Methods. Cross sectional study in Hispanic elderly (60+y) and adult (18-50y) recent TB contacts (ReC) or c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Our findings call for the need to consider the elderly in a similar high-risk category. A recent study showed that Interferon-gamma release assays (IGRA) are effective for identification of latent TB infection in the elderly [57]. We also identified modifiable sociodemographic factors associated with higher odds of death during TB in the elderly, such as excess alcohol use or low BMI.…”
Section: Discussionmentioning
confidence: 90%
“…Our findings call for the need to consider the elderly in a similar high-risk category. A recent study showed that Interferon-gamma release assays (IGRA) are effective for identification of latent TB infection in the elderly [57]. We also identified modifiable sociodemographic factors associated with higher odds of death during TB in the elderly, such as excess alcohol use or low BMI.…”
Section: Discussionmentioning
confidence: 90%